Winter meltwater storage on Antarctica’s George VI Ice Shelf and tributary glaciers, from synthetic aperture radar - Deakin, Katherine A.; Willis, Ian C.; Dell, Rebecca L. (Frontiers in Earth Science, 2025)
The presence and storage of meltwater on Antarctic ice shelves has implications for ice-shelf stability and collapse, while meltwater on grounded tributary glaciers, if able to access the bed, could affect their dynamics. Given the significance of Antarctica’s ice shelves for grounded ice contributions to global mean sea levels, there have been many efforts to map their meltwater extents, whereas far fewer efforts have been made to map water on Antarctica’s grounded ice. Most previous mapping has used optical imagery, which is limited to mapping surface water on cloud-free days during the austral summer. Conversely, research into the prevalence of wintertime and shallow subsurface meltwater storage is scarce. Here, we analyse synthetic aperture radar (SAR) backscatter time series between 2015 and 2021 for a selected number of large, late- and early-summer meltwater bodies on George VI Ice Shelf (GVIIS) and surrounding glaciers through intervening winters. Variable rates of surface or shallow subsurface freeze-through and melt onset are identified, alongside two locations where meltwater appears to have been stored throughout the 2019 winter. One of these sites, a large shallow subsurface meltwater body on grounded ice, appears to have retained liquid water throughout all 6 years, including during winter. This site would be valuable for further exploring how surface and shallow subsurface meltwater bodies may influence Antarctic glacier dynamics through drainage to the bed.